Parents’ views on child physical activity and their implications for physical activity parenting interventions: a qualitative study - Bentley, Georgina F (BioMed Central, 2012)
BACKGROUND: Establishing healthy physical activity (PA) behaviours in early childhood is important for future PA behaviours. Parents play a central role in young children’s PA. However, there is currently little research on parenting interventions to increase child PA. This study was formative work to inform the content of a pilot randomised-controlled trial. METHODS: In-depth telephone interviews were carried out with 32 parents of 6 to 8 year old children residing in two areas that varied in their socio-economic characteristics, in Bristol, UK. Data were analysed thematically using a framework approach. RESULTS: Most parents described their child as being active or very active and indicated that they did not perceive a need for an increase in their child’s PA. Parents used a variety of visual cues to make this judgement, the most common being that they perceived their child as having lots of energy or that they did not view them as overweight. Parents reported environmental factors such as monetary cost, time constraints, lack of activity provision and poor weather as the main barriers to their child’s PA. Parental support and child’s enjoyment of PA appeared to be important facilitators to children participating in PA. CONCLUSION: Improving parents’ knowledge of the PA recommendations for children, and increasing their awareness of the benefits of PA beyond weight status may be an important first step for a parenting PA intervention. Although parents commonly perceive environmental factors as the main barriers to their child’s PA, parental concern about low levels of child PA, their capacity to support behaviour change, child motivation, self confidence and independence may be key areas to address within an intervention to increase child PA. Effective methods of helping parents address the latter have been developed in the context of generic parenting programmes.